2011
DOI: 10.1111/j.1754-8845.2011.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation and experience: Two pedagogical interventions observed

Abstract: In light of the hard times in which literary education has been finding itself, this paper evaluates the merits of two instructional interventions. It describes an experiment which contrasts interpretive and experiential approaches to reading carried out with 17 Comparative Literature Canadian university students. Two different sets of pre-reading and reading instructions were prepared. The group working under the control condition followed a set of 'interpretive instructions' while the one working under the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…This may have important implications for the potential of using literature in specific environments, for example, teachers' professional development (Kooy, 2006), people's professional behavior in general (Bal, Butterman & Bakker, 2011), and domainspecific education in literary studies (e.g., Fialho, Zyngier & Miall, 2011;Fialho, Miall & Zyngier, 2012) as well as the secondary literature classroom that forms the context for the present study.…”
Section: Reading Literary Fiction: Changes In Self and Social Perceptmentioning
confidence: 99%
See 2 more Smart Citations
“…This may have important implications for the potential of using literature in specific environments, for example, teachers' professional development (Kooy, 2006), people's professional behavior in general (Bal, Butterman & Bakker, 2011), and domainspecific education in literary studies (e.g., Fialho, Zyngier & Miall, 2011;Fialho, Miall & Zyngier, 2012) as well as the secondary literature classroom that forms the context for the present study.…”
Section: Reading Literary Fiction: Changes In Self and Social Perceptmentioning
confidence: 99%
“…Other distinctions have been made as well, such as an interpretative versus an experiential approach (Fialho, Zyngier & Miall, 2011;Fialho, Miall & Zyngier, 2012), while other scholars have argued for bridging the gap by attending both to meaning of literary texts as well as bringing personal experiences to these texts (Wilhelm, 2007), for example by creating 'a social community that supports learning literature' (Beach et al, 2011, p. 8). Similarly, Van de Ven and Doecke (2011) noted that the teachers in their study connected the interpretation of literary texts to 'the need to negotiate the social relationships that comprise any classroom' (p. 219).…”
Section: Teachers' Approaches To Literature Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be partly due to the assumption, traditionally prevailing in the literary academia, that reading is meant to primarily serve systematic, analytical, distanced reflection (see, e. g., Fialho, Zyngier, and Miall 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The kind of meaning at stake is to be understood quite broadly, so as to include any response toward the personal relevance of the story for the individual reader and other forms of »lived« or »experienced« signification (see e. g. Seilman and Larsen 1989;Miall 2006). As empirical research into the effects of pedagogical interventions has shown (Fialho/Zyngier/Miall 2011), this is how the general concept of interpretation may be widely understood amongst first-year (Canadian) university students of literature. When assessing classes where personal response to text was expressly encouraged, they were found to report more focus on »analysis and interpretation«, compared to their assessment of classes encouraging impersonal, analytic commentary only.…”
mentioning
confidence: 99%